Coronavirus disease 2019 and cardiovascular system: A narrative review. (August 2020) - Kwenandar, Felix; Japar, Karunia Valeriani; Damay, Vika; Hariyanto, Timotius Ivan; Tanaka, Michael; Lugito, Nata Pratama Hardjo; Kurniawan, Andree
Abstract: At the end of 2019, a viral pneumonia disease called coronavirus disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV2), emerged in Wuhan, China. This novel disease rapidly spread at an alarming rate that as a result, it has now been declared pandemic by the World Health Organization. Although this infective disease is mostly characterized by respiratory tract symptoms, increasing numbers of evidence had shown considerable amounts of patients with cardiovascular involvements and these were associated with higher mortality among COVID-19 patients. Cardiac involvement as a possible late phenomenon of the viral respiratory infection is an issue that should be anticipated in patients with COVID-19. Cardiovascular manifestation in COVID-19 patients include myocardial injury (MI), arrhythmias, cardiac arrests, heart failure and coagulation abnormality, ranging from 7.2% up to 33%. The mechanism of cardiac involvement in COVID-19 patients involves direct injury to myocardial cells mediated by angiotensin-converting enzyme 2 (ACE2) receptors as suggested by some studies, while the other studies suggest that systemic inflammation causing indirect myocyte injury may also play a role. Combination of proper triage, close monitoring, and avoidance of some drugs that have cardiovascular toxicity are important in the management of cardiovascular system involvement in COVID-19 patients. The involvement of the cardiovascular system in COVID-19 patients is prevalent, variable, and debilitating. Therefore, it requires our attention and comprehensive management.